2013
DOI: 10.1007/s12010-013-0351-7
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antibacterial and Antibiofilm Effect Between (+)-Medioresinol and Antibiotics In Vitro

Abstract: In this study, antibacterial effects of (+)-Medioresinol isolated from stem bark of Sambucus williamsii and its synergistic activities in combination with antibiotics such as ampicillin, cefotaxime, and chloramphenicol were tested by antibacterial susceptibility testing and checkerboard assay. (+)-Medioresinol possessed antibacterial effects against antibiotics-susceptible- or antibiotics-resistant strains. Most of combinations between (+)-Medioresinol and each antibiotic showed synergistic interaction (fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Compound 1698 was characterized as a furofuran type lignan, pinoresinol, glycosidically linked to a disaccharide, rutinose. Previously, anti-biofilm activity of another furofuran lignan, (+)-medioresinol, against P. aeruginosa and E. coli has been demonstrated [ 48 ], but so far, anti-QS activity against C. violaceum has not been reported, to the best of our knowledge. Compound 2307 comprises an aminothiazole linked to an indole moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 1698 was characterized as a furofuran type lignan, pinoresinol, glycosidically linked to a disaccharide, rutinose. Previously, anti-biofilm activity of another furofuran lignan, (+)-medioresinol, against P. aeruginosa and E. coli has been demonstrated [ 48 ], but so far, anti-QS activity against C. violaceum has not been reported, to the best of our knowledge. Compound 2307 comprises an aminothiazole linked to an indole moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Also, pinoresinol treatment up-regulated osteogenic differentiation and mineralization of the extracellular matrix via BMP-2/MAPK/β-catenin signaling pathway ( Park et al, 2020 ). Medioresinol was not found to be effective in treating PMOP but was reported that possessed antifungal function, leishmaniasis activity, and cardiovascular disease risk reduction ( Hwang et al, 2012 ; Hwang et al, 2013 ). All this literature supported the above-mentioned consequences of Bu-Yang herbs promoted BMD and bone microarchitecture in treating PMOP.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial effect of F1 could be associated with medioresinol because it acts against strains sensitive or resistant to antibiotics. Therefore, it could be used as a therapeutic agent for bacterial infections [ 65 ]. However, its effect could also be associated with caffeic acid 4- O -glucoside and 3-hydroxyfloretin 2′- O -glycoside because caffeic acid 4- O -glucoside has activity on B. cereus , Bacillus subtilis , S. aureus , P. aeruginosa , E. coli , and K. pneumonia [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ABTS assay (2,2 -azino-bis (3-ethylbenzothiazoline-6-sulfonic acid)) was adapted to a 96-well microplate and performed with 50 µM ABTS and a TROLOX calibration curve (45,65,85,105,125,145,165, and 185 mg/L). The extract and fractions were prepared at 1000 µg/mL.…”
Section: Abts Radical Scavenging Methodsmentioning
confidence: 99%